War in Ukraine vs. Motherhood: Mental health self-perceptions of relocated pregnant women and new mothers - Liudmyla Krupelnytska; Alona Vavilova; Nazar Yatsenko; Magdalena Chrzan-Dętkoś; Olha Morozova-Larina; Ana Uka; Maria F. Rodríguez-Muñoz (BMC Pregnancy and Childbirth)
Abstract Background The Russian military’s carnal crimes render certain Ukrainian areas uninhabitable. As a result, a significant portion of the population is experiencing stress-related issues caused by hostilities and forced displacement. This research aimed to examine the self-assessed mental health of pregnant women and new mothers (PNM) who faced relocation. Methods This report presents findings from a study conducted as part of the Perinatal Mental Health for Refugee Women (PMH-RW) Project. This cross-sectional study used data from 191 PNM who are either internally displaced persons (IDP) or refugees (REF). Results A higher number of REF than IDP were from the capital, but fewer from rural communities, and new mothers were more likely to hail from major cities than pregnant women. The discrepancy in migration options likely causes the frequent relocation of some groups to inadequately equipped areas, thereby increasing their vulnerability. For example, REF experienced far less pregnancy complications than IDP. The Gini coefficient of 0.153 suggests minor income inequality among the respondents. However, there is a stark contrast between this relatively low inequality and the substantial reports on worsened financial conditions post-invasion. This finding underscores the significant impact of war-related financial instability on the perceived distress of pregnant women and new mothers, with financial burdens emerging as a primary predictor of their distress. Conclusion The financial burden and socio-economic background of pregnant and new mothers during wartime migration can define their mental health resilience. The inconsistent availability of essential resources caused by wartime economic woes significantly influences the perceived well-being of PNM.